The Effect of Good Corporate Governance, Free Cash Flow, and Tax Planning on Earnings Management - Agriyanto, Ratno; Setiyawati, Azizah; Farida, Dessy Noor (At-Taqaddum, 2021)
Earnings is one of the management assessment tools as a form of responsibility to investors, thus allowing opportunistic behavior to do earnings management. The study aims to determine the effect of good corporate governance, free cash flow, and tax planning on earnings management. In this study, the independent variables are the board of independent commissioners, institutional ownership, audit committee, free cash flow, and tax planning. The dependent variable is earnings management which is projected through discretionary accruals using the modified Jones model. Data collected in this study used the documentation method and library method. The object of this study is state-owned companies listed in the 2014-2018 period of the Indonesian Stock Exchange. The sampling technique used purposive sampling, and the analysis technique used multiple linear. This study shows that a partial board of independent commissioners, institutional ownership, audit committee, and tax planning do not significantly affect earnings management. In contrast, free cash flow has a significant negative impact on earnings management. Therefore, implementing good corporate governance, free cash flow, and tax planning which is not just to fulfill existing regulations, will increase performance and company value and trust of investors.